A model for measuring the quality of public policies in innovation - Pakes, Paulo Renato; Torkomian, Ana Lúcia Vitale; Silva, Brena Bezerra; Borrás, Miguel Ángel Aires; Bianchini, Vívian Karina; Razzino, Carlos do Amaral (Brazilian Journal of Operations & Production Management, 2024)
Goal : This article presents a model for measuring the quality of public policies on innovation and its validation in a public policy on technology parks (SPTec) Design/methodology/approach: A survey on the quality of public policy SPTec was carried out. Through descriptive analysis, it was possible to verify the quality of public policy in five determinants of quality. Factor analysis allowed the regrouping of quality attributes into new determinants for SPTec public policy. Finally, the multiple regression analysis allowed us to analyze the dependence relationship between the variables. Results: The public policy SPTec is immature in terms of process quality, quality of the relation, and quality of the result. In addition, we identified the determinants that should be prioritized in the implementation of SPTec public policy in a possible reformulation. Finally, the attributes of quality that generate the greatest effect in terms of an increase in user satisfaction are shown, as well as those that generate a decrease in satisfaction if they have an increase in their performance. Limitations of the investigation: Because of the chosen research approach, the research results may lack generalizability. Therefore, researchers are encouraged to test the proposed propositions further. Practical implications: As a limitation, there is the fact that the factor analysis of public policy SPTec can only be generalized at the level of the same. Likewise, the presented model for measuring quality in the public sector requires adaptation for each public policy analyzed. Originality/value: This article fills a gap regarding the lack of instruments for measuring the quality of public policies in innovation systems.